INTEGRASI STEM BERBASIS CANVA SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR IPAS PADA MATERI TUMBUHAN - Ramadhani Mahfudha, Radalah; Nuruddin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning in Natural and Social Sciences (IPAS) at the elementary school level requires engaging learning experiences that are relevant to real-life contexts and encourage students’ active participation in the learning process. However, classroom practices often indicate that IPAS instruction remains heavily textbook-centered, resulting in less optimal student learning outcomes. The integration of the STEM approach with the use of Canva as a learning medium represents a strategic alternative that has the potential to enhance creativity, conceptual understanding, and student engagement. This study was conducted to identify the effect of implementing a Canva-based STEM approach on IPAS learning outcomes, particularly on plant material, among fourth-grade students of SDN Pundong 2 Jombang. The research employed a quantitative method using a Pre-Experimental One Group Pretest–Posttest design. The participants consisted of 20 students. The research instrument was a learning achievement test administered before and after the intervention. Data analysis was conducted using a Paired Sample t-test. The findings revealed an improvement in students’ learning outcomes after the implementation of the Canva-based STEM learning approach. The results indicate that the use of Canva as a digital design medium through project-based activities significantly enhances students’ understanding of plant structure, the functions of plant parts, and growth processes. Therefore, IPAS learning based on STEM and Canva can be recommended as an effective strategy to improve learning achievement and student participation at the elementary school level.